Lactoferrin and Nanotechnology: The Potential for Cancer Treatment - Tuan Hiep Tran; Phuong Thi Thu Tran; Duy Hieu Truong (Pharmaceutics, 2023)
Lactoferrin (Lf)—a glycoprotein of the transferrin family—has been investigated as a promising molecule with diverse applications, including infection inhibition, anti-inflammation, antioxidant properties and immune modulation. Along with that, Lf was found to inhibit the growth of cancerous tumors. Owing to unique properties such as iron-binding and positive charge, Lf could interrupt the cancer cell membrane or influence the apoptosis pathway. In addition, being a common mammalian excretion, Lf offers is promising in terms of targeting delivery or the diagnosis of cancer. Recently, nanotechnology significantly enhanced the therapeutic index of natural glycoproteins such as Lf. Therefore, in the context of this review, the understanding of Lf is summarized and followed by different strategies of nano-preparation, including inorganic nanoparticles, lipid-based nanoparticles and polymer-based nanoparticles in cancer management. At the end of the study, the potential future applications are discussed to pave the way for translating Lf into actual usage.